Elaboración e implementación de una estrategia didáctica- pedagógica para la promoción de la higiene oral, dirigida a los agentes educativos del Nidos de Paz el Dorado de Comfacauca de la ciudad de Popayán (2021)
Among the programs of Foniñez, developed by the Family Compensation Fund of Cauca - Comfacauca, is the Comprehensive Care Program for Children - A.I.N., which aims to strengthen the processes aimed at training children in their early childhood, through early education focused on pedagogy, promotion and prevention in health, nutrition, recreation, protection and care; which allows them to improve their quality of life and social welfare. In order to have a broader view of the program and to start the construction and execution of this project, we got to know the two intervention strategies called Nidos de Paz (Ministry of Social Protection 2008) and the CAIF (Comprehensive Family Care Center), so, according to the dynamics of the program, socio-demographic location, easy access and number of population, we worked with the Nido de Paz El Dorado; to identify if they have simple and timely strategies that serve to promote good practices in oral health of children attending the program. It is also considered that children's oral hygiene is the responsibility of adults, at least until the child has adequate motor skills to perform these procedures. It is estimated that this responsibility is until the child is 8 or 10 years old. Hence the importance for parents to have basic knowledge about oral hygiene and how to perform the care procedure that contributes to generate a positive change in the oral health of their children. Likewise, teachers should acquire tools that contribute to the development of these healthy practices, since children spend most of their time at the Nido de Paz El Dorado, where the teacher is a fundamental part of their wellbeing. Therefore, it is urgent to implement programs or projects aimed at a healthy education, where parents are directly responsible for promoting oral health in children.